Energetic Neutral and Charged Particle Measurements in the Inner Saturnian Magnetosphere During the Grand Finale Orbits of Cassini 2016/2017. Issue 20 (20th October 2018) - Krupp, N.; Roussos, E.; Kollmann, P.; Mitchell, D. G.; Paranicas, C. P.; Krimigis, S. M.; Hamilton, D. C.; Hedman, M.; Dougherty, M. K.
Abstract: We give an overview of the charged and neutral particle measurements during the Grand Finale of Cassini performed by the Magnetosphere Imaging Instrument, MIMI, on board. The first in situ measurements of MeV particles between the D‐ring and the atmosphere of the planet showed protons with energies above 300 MeV with higher count rates when magnetically connected to the D‐ring which was less dense than expected, while more material was present at the inner edge. The variability in the count rates was a combination of sensor look direction, pitch angle coverage, changes in the L‐range, and latitude. Enhanced emissions of energetic neutral atoms during ring current activity was detected and confirmed the existence of a low‐energy ion radiation belt discovered by Cassini in 2004. No detection of low‐energy ions was indicative of a source population from a region closer than 1, 800 km above the 1 bar cloud level. Plain Language Summary: We use neutral and charged particle measurements between Saturn's atmosphere and the rings during Cassini's Grand Finale to characterize Saturn's innermost radiation belt. We find a less dense D‐ring as expected with a very dense inner edge due to the presence of the D68 ringlet. We also confirmed the existence of a low‐energy ion inner belt through energetic neutral atom emissions which appear to be enhanced during magnetospheric activity. We could constrain the region of the inner belt to be closer than 1, 800 km above the 1 bar cloud level. Key Points: We report on the first in situ measurements of MeV charged particles between Saturn and the D‐Ring with a strong absorption of particle fluxes caused by the D68 Ringlet on the inner edge of the D‐Ring We found a low‐energy proton radiation belt below 1, 800 km with respect to the 1 bar cloud level of Saturn's atmosphere by using Energetic Neutral Atom (ENA) emissions Low‐altitude ENA emission correlates to ring current activity